1999
DOI: 10.1002/1531-8257(199901)14:1<45::aid-mds1009>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine induces changes in GPi spontaneous outflow in patients with parkinson's disease

Abstract: OBJECTIVE: To determine the effect of a single dose of apomorphine on internal globus pallidus (GPi) neuronal discharge in patients with Parkinson's disease (PD).PATIENTS AND METHODS: Nine PD patients who underwent microelectrode-guided posteroventral pallidotomy (PVP) were studied. After identification of a single GPi unit discharge with sufficient spike S/N ratio to allow reliable thresholding, basal recording was followed by a single 3-mg subcutaneous injection. One-minute samples were recorded 10Ј, 30Ј, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…Interestingly, an increased irregularity of spontaneous firing was also indicated by intrasurgical recordings of GPi neurons in patients with generalized dystonia when compared with patients suffering from idiopathic Parkinson's disease (Vitek et al, 1999). Additionally, a change in the pattern of GPi neurons was reported for Parkinson's disease patients developing drug-induced dyskinesias (Merello et al, 1999).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, an increased irregularity of spontaneous firing was also indicated by intrasurgical recordings of GPi neurons in patients with generalized dystonia when compared with patients suffering from idiopathic Parkinson's disease (Vitek et al, 1999). Additionally, a change in the pattern of GPi neurons was reported for Parkinson's disease patients developing drug-induced dyskinesias (Merello et al, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…put activity is hypothesized (Mitchell et al, 1990;Wichmann and DeLong, 1996;Suarez et al, 1997;Berardelli et al, 1998;Crossman and Brotchie, 1998;Hallett, 1998;Merello et al, 1999;Filion, 2000;Vitek and Giroux, 2000).…”
mentioning
confidence: 99%
“…The normal GPi firing rate in primates is in the range 60-90 s −1 , with an increase of about 10-20 s −1 after MPTP treatment in monkeys (Filion and Tremblay, 1991;Heimer et al, 2002;Yoshida, 1991). In line with these results, normalization of dopamine levels by application of the dopamine agonist apomorphine decreases the average firing rate of GPi neurons in PD patients (Merello et al, 1999). On the other hand, some studies found no significant change in average firing rates of GPi (Bergman et al, 1994;Wichmann et al, 1999) or its rodent homolog, the entopeduncular nucleus (EP) (Robledo and Feger, 1991).…”
Section: Data On Firing Rates In Normal and Parkinsonian Statesmentioning
confidence: 82%
“…Firing rates of the internal segment of the GP (GP i ) cells are increased, whereas the external segment of the GP (GP e ) cells display decreased firing rates (Miller and DeLong, 1987;. Single-electrode recordings performed on human parkinsonian patients during surgical interventions designed to relieve parkinsonian symptoms indicate trends in firing rates similar to those found in primates (Hutchison et al, 1994;Merello et al, 1999).…”
mentioning
confidence: 91%
“…Many electrophysiological studies have indicated that the changes of pallidal firing rates are reversed after administration of dopamine replacement therapy (DRT) in humans (Hutchinson et al, 1997;Merello et al, 1999;Levy et al, 2001) and primates Papa et al, 1999) (but see Boraud et al, 1998). However, all of these studies were confined to the activity of single neurons.…”
mentioning
confidence: 99%